Acute Catecholamine Exposure Causes Reversible Myocyte Injury Without Cardiac Regeneration. Issue 7 (16th September 2016) - Wallner, Markus; Duran, Jason M.; Mohsin, Sadia; Troupes, Constantine D.; Vanhoutte, Davy; Borghetti, Giulia; Vagnozzi, Ronald J.; Gross, Polina; Yu, Daohai; Trappanese, Danielle M.; Kubo, Hajime; Toib, Amir; et al.
Abstract : Rationale : Catecholamines increase cardiac contractility, but exposure to high concentrations or prolonged exposures can cause cardiac injury. A recent study demonstrated that a single subcutaneous injection of isoproterenol (ISO; 200 mg/kg) in mice causes acute myocyte death (8%–10%) with complete cardiac repair within a month. Cardiac regeneration was via endogenous cKit + cardiac stem cell–mediated new myocyte formation. Objective : Our goal was to validate this simple injury/regeneration system and use it to study the biology of newly forming adult cardiac myocytes. Methods and Results : C57BL/6 mice (n=173) were treated with single injections of vehicle, 200 or 300 mg/kg ISO, or 2 daily doses of 200 mg/kg ISO for 6 days. Echocardiography revealed transiently increased systolic function and unaltered diastolic function 1 day after single ISO injection. Single ISO injections also caused membrane injury in ≈10% of myocytes, but few of these myocytes appeared to be necrotic. Circulating troponin I levels after ISO were elevated, further documenting myocyte damage. However, myocyte apoptosis was not increased after ISO injury. Heart weight to body weight ratio and fibrosis were also not altered 28 days after ISO injection. Single- or multiple-dose ISO injury was not associated with an increase in the percentage of 5-ethynyl-2′-deoxyuridine–labeled myocytes. Furthermore, ISO injections did not increase new myocytes in cKit +/Cre ×R-GFP transgenic mice. Conclusions : A single dose of ISO causes injury in ≈10% of the cardiomyocytes. However, most of these myocytes seem to recover and do not elicit cKit + cardiac stem cell–derived myocyte regeneration. Abstract : Supplemental Digital Content is available in the text.